Masterplan Air Limbah Kawasan Bukit Semarang Baru (BSB) Kota Semarang - Priska Septiana (Jurnal Teknik Lingkungan, 2013)
Waste water is a residual water that produced by an industrial production  process and domestic (household) sometimes it existence at a time and certain place environmentally undesirable. because it has no economic value. This masterplan aims to manage waste water especially grey water to overcome sanitation issues. This masterplan was examined based on five aspects : institutional, technical, socio-economic, finance, and the environtmental. It was planned to buid two IPAL,  where  located in Jatisari and Mijen, and also chanelling of waste water by the low of gravity. Based on scale priorities, criteria that involve aspects of population density, existing conditions, and socio-economic conditions, the major priority is to handle  Jatisari area, and afterwards Mijen area.